DRIFT and Theoretical Studies of Ethylene/Ethane Separation on Flexible and Microporous [Cu2(2, 3‐pyrazinedicarboxylate)2(pyrazine)]n. Issue 17 (June 2014) - Kishida, Keisuke; Watanabe, Yumiko; Horike, Satoshi; Watanabe, Yoshihiro; Okumura, Yoshikuni; Hijikata, Yuh; Sakaki, Shigeyoshi; Kitagawa, Susumu
Abstract: Invited for the cover of this issue is the group of Susumu Kitagawa at Kyoto University. The cover image shows the adsorption‐based separation of ethylene from ethane by [Cu2 (2, 3‐pyrazinedicarboxylate)2 (pyrazine)] n . The background is a view of the Oita chemical complex where cryogenic distillation of ethylene is conducted daily. Our research laboratory, belonging to Showa Denko, is located at this complex. Abstract : We believe in the vast potential of PCPs for industrial application including in gas separation... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 2747 ff .